2015
DOI: 10.4236/fns.2015.62025
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, Nutritional, Organoleptic Characteristics and Food Applications of Four Mango (<i>Mangifera indica</i>) Varieties

Abstract: Physicochemical characteristics of four varieties of mango (Julie, Bassignac, Green and Moussache) from Martinique (F.W.I.) were examined at three ripening stages. All ripening protocols studied showed an evolution in parameters between the harvesting and the expandable stage. Fruit and pulp firmness, starch and vitamin C contents decreased whereas pulp pH and carotenoids content increased. Only fruit size and polyphenols content were the same during the ripening. Bassignac and Julie varieties were richer in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 9 publications
1
15
1
1
Order By: Relevance
“…The uniformity of ripening can be characterized by measuring texture and the brix (ratio soluble dry extract/titratable acidity) [12]. Reference [13] reported that there is no direct correlation between the maturity of the fruit and the colour of the skin of the fruits. were examined at three ripening stages [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The uniformity of ripening can be characterized by measuring texture and the brix (ratio soluble dry extract/titratable acidity) [12]. Reference [13] reported that there is no direct correlation between the maturity of the fruit and the colour of the skin of the fruits. were examined at three ripening stages [13].…”
Section: Introductionmentioning
confidence: 99%
“…Reference [13] reported that there is no direct correlation between the maturity of the fruit and the colour of the skin of the fruits. were examined at three ripening stages [13]. In Egypt, some major local and imported grown mango cultivars were characterized phsico-chemically to assess the genetic variability and heritability [14].…”
Section: Introductionmentioning
confidence: 99%
“…Mangoes of the ''Belle-Dame'' variety are dark-green fruits in the mature, unripe state. They become yellowishgreen and yellow when they are respectively ripe and too ripe [18]. This variety was chosen because of its commercial importance and for its availability at the time of the study (March 2018).…”
Section: Plant Materialsmentioning
confidence: 99%
“…vitamin C ranged between 46.53 mg/100 g and 26.53 mg/100g, potassium ranged from 10.29 mg/100 g and 64.04 mg/100 g and calcium ranged between 6.54 mg/100g and 30.56 mg/100 g. These bio-parameters were depended on mango verity. Ellong et al (2015) revealed that firmness, taste, and pH properties correlated with mango varity, as well as starch, carbohydrates fractions, carotenoids, phenolic compounds, vitamins C and E contents. Wongmetha et al (2015) stated that sucrose metabolism and starch storage in mango were depended on growth stage, development in mango fruits, decrease activity of sucrose phosphate syntheses, acid invartase (AI) and neutral invartase (NI).…”
Section: Introductionmentioning
confidence: 97%